(untitled) (Sains Humanika, 2015)
This paper investigates teleworking, its benefits and challenges briefly, and effect on organizational control. Some issues related to teleworking such as flexible work time and its effect on employees Attitudes to teleworking has been discussed. In this line, three stages of teleworking and the changing expectations of management and staff will be explained. Based on these studies, a model for understanding organizational change process will be offered. The model may be utilized by managers during implementation of teleworking in an organization. Also the model suggests appropriate solutions to the challenges exposed by decreasing employee satisfaction following institutional control at every stage of teleworking.